Sekuen Gen Surface Antigen-1 dan Bradizoit Antigen-1 Takizoit Toxoplasma gondii sebagai Kandidat Pemindai DNA (SAG1 AND BAG1 GENE SEQUENCES ANALYSIS OF TOXOPLASMA GONDII TACHYZOITE AS PROBE CANDIDATE) - Apsari, Ida Ayu Pasti; Artama, Wayan Tunas; ., Sumartono; Damriyasa, I Made (Jurnal Veteriner, 2013)
Sag1 and bag1 is a gene specific-stage for Toxoplasma gondii tachyzoite and bradyzoite. The purposeof this study was analyze the sequences of sag1 and bag1 tachyzoite genes of local of Toxoplasma gondiiisolate as deoxyribonucleic acid probe candidate. Tachyzoite of local of Toxoplasma gondii isolate used onthis study. Gene sag1 and bag1 gene of Toxoplasma gondii were amplified by PCR, and then sequenced. Theresults showed sag1 fragment gene contained 612 bp and bag 1 contained 470 bp in length. BLAST analysisof sag1 and bag1 gene fragments as probe candidate showed that high specific for Toxoplasma gondii andno significant cross-reaction fragment with host and other parasites. The sequences 136 bp and 98 bpfragments as DNA probe candidate of Toxoplasma gondii sag1 and bag1 respectively.
Keywords: Sag1 gene, Bag1 gene, tachyzoite, Toxoplasma gondii, DNA probe